Inflammatory Serum Biomarkers in Colorectal Cancer in Kazakhstan Population - L. Akhmaltdinova; V. Sirota; V. Zhumaliyeva; D. Babenko; I. Kadyrova; Z. Tauesheva; D. Taizhanova; A. Ibraeva; M. Maratkyzy; A. Turmukhambetova (International Journal of Inflammation)
Colorectal cancer is a type of oncopathology widespread in Kazakhstan. The genetic component, as well as the possible etiopathogenetic mechanisms, is widely studied. One of the most promising areas is the study of diagnostic and prognostic possibilities of inflammatory biomarkers in patients with different degrees of tumor differentiation. The following biomarkers were included in the study panel: stem cell factor (SCF), vascular endothelial growth factor (VEGF), fibroblast growth factor (FGF2), interleukin 6 (IL6), interleukin 8 (IL8), macrophage migration inhibitory factor (MIF), soluble Fas (SFAS), soluble Fas ligand (sFASL), transforming growth factor β (TGF), tumor necrosis factor (TNF), TNF-related apoptosis-inducing ligand (TRAIL), and programmed death ligand 1 (PD-L1). The data of our study show that most of the basic proinflammatory cytokines are involved in the systemic process and their levels do not depend on the level of tissue differentiation. Serum PD-L1 has shown itself to be a promising marker for tumor growth, which depends on the degree of differentiation.